La inteligencia artificial y su aporte en los procesos de enseñanza-aprendizaje en los estudiantes del cuarto año EGB de la Unidad Educativa Emigdio Esparza Moreno, Babahoyo 2023 - Pérez Rosado, Shirley Lilibeth (2023)
The case study focuses on the Emigdio Esparza Moreno Educational Unit, where artificial intelligence and its contribution to the teaching-learning processes in fourth grade students (EGB) is analyzed. As an objective of the research, the institution faces obstacles in the effective implementation of AI, such as lack of teacher training, insufficient technological infrastructure and resistance to change in traditional teaching methodologies, applied to fourth year students (EGB) of the mentioned Educational Unit. It is framed in the line of study of the educational model and the sub-line Methods, Techniques and Strategies of Teaching-Learning, and investigates the incorporation of AI in education and its influence on learning and academic performance. It recognizes benefits such as the personalization of teaching and identifies areas for improvement in teacher training and technological infrastructure. In the context of contemporary technological developments, this case study provides a comprehensive overview of how artificial intelligence is being incorporated into education and how this impacts the teaching-learning processes and academic growth of fourth grade GBS students.